A utilização do Arco de Maguerez como estratégia problematizadora para o ensino de química: uma alternativa para a desmistificação da química - Santos, Paulo Eduardo Netto dos (2023)
Often, common sense perceives scientific knowledge as intangible and distant from reality. However, this knowledge is applied in fundamental fields of society, such as medicine and technological development. The objective is to develop a methodological proposal based on the Maguerez’s Arch that can contribute to the demystification of chemistry and its professionals. As it has impacts in various areas, the theme of Drugs was chosen. Activities such as diagnostic questionnaire, group discussions, experiments, and discussions on topics such as the definition of the term "drug," its historical consumption, and the development of medicinal drugs were carried out. The proposal included the design, development, and execution of an activity by the students with the aim of stimulating creativity, reflections, and critical and analytical thinking, attributes expected in Basic Education. The problematization carried out through the Maguerez’s Arch stimulated the expected interest and reflections, as evidenced by discussions on the importance of chemistry, other sciences, and their professionals. Consequently, epistemological conflicts were developed regarding the students’ social representations of scientific knowledge. Therefore, it is important for Science Education to be conducted in an environment that includes contextualized discussions on relevant topics for the students.